Nucleation, Rapid Folding, and Globular Intrachain Regions in Proteins - Wetlaufer, Donald B. (1973)
Distinct structural regions have been found in several globular proteins composed of single polypeptide chains. The existence of such regions and the continuity of peptide chain within them, coupled with kinetic arguments, suggests that the early stages of three-dimensional structure formation (nucleation) occur independently in separate parts of these molecules. A nucleus can grow rapidly by adding peptide chain segments that are close to the nucleus in aminoacid sequence. Such a process would generate three-dimensional (native) protein structures that contain separate regions of continuous peptide chain. Possible means of testing this hypothesis are discussed.